Reflections on the SARS-Covid-2 pandemic after one year: Predictable, preventable but inevitable: an ecologist's perspective - Jeffrey Harvey (The Central European Review of Economics and Management (CEREM), 2021)
Aim: The major aim of the current essay is to argue that neoliberal capitalism, by virtue of its core tenets, has significantly increased the risk of disease outbreaks like SARS-Covid-2. Conclusion/Finding: The dominant socio-political-economic system across the industrialized world is neoliberal capitalism that focuses on economic growth and profit maximization. These are obtained in part through the weakening or elimination of environmental regulations. Although neoliberalism has brought benefits to some, it has exacerbated social and economic divisions within and between countries. More importantly, it is undeniably responsible for increasing the rate of environmental destruction, especially in developing countries in the south, which are rich is resources and raw materials coveted by multinational corporations based in the western developed countries. The loss and/or fragmentation of ecosystems is also bringing people into closer contact with many species that were once largely insulated from human communities, such as bats, that harbor harmful viruses with the potential to affect people through zoonotic spill-over via another wild or domesticated species. Originality/Value of Article: Because it eschews the precautionary principle, neoliberal capitalism is uniquely ill-equipped to prepare for potential calamities like pathogenic outbreaks and, more worryingly, climate change. This makes it obsolete in the Anthropocene. We need to seriously work towards making structural changes in the socio-political landscape in ways that reduce the damage we are doing and also strive to create social justice across the world. This is imperative if we are to create a sustainable future and to protect much of the living world from destruction.
Keywords: F64; P10; Q54; 330; climate change; environmental destruction; extinction; habitat; neoliberal capitalism; profit